Penerapan strategi digital public relation dalam membangun citra positif bank syariah di media sosial - Anggraini, Jesika Devi Mufita (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of digital public relations strategies in building a positive image for Islamic banks in the digital era. The increasing use of social media requires Islamic financial institutions to adapt effective, fast, and interactive communication strategies. Using a descriptive qualitative approach adapted from previous research, this article examines the external and internal strategies implemented by Bank Syariah Indonesia to strengthen engagement and increase public trust. The study results indicate that the digital Public Relation strategy is implemented through optimizing online publications, collaborating with influencers, and disseminating Islamic values ​​on social media. Furthermore, strengthening internal communication contributes to establishing a positive work culture and strengthening the institution’s credibility in the public eye. The implementation of digital public relations has proven effective in creating a sustainable positive image and building customer loyalty to Islamic banking products and services.